2020
DOI: 10.1186/s41938-020-0211-z
|View full text |Cite
|
Sign up to set email alerts
|

First detection of the Nearctic parasitoid species Trichopoda pennipes (Fabricius) (Diptera: Tachinidae) in Egypt

Abstract: Specimens of the feather-legged fly, Trichopoda pennipes (Fabricius) (Diptera: Tachinidae), which parasitize adults of the southern green stink bug Nezara viridula (L.) (Hemiptera: Pentatomidae), have been detected in Giza, Egypt. This is the first record of this Nearctic species with its genus (Trichopoda) and its tribe (Gymnosomatini) in Egypt. T. pennipes is known as an endoparasitoid of many true bug hosts, the pests of various crops, and it could have a potentiality to control these pests in addition to N… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 15 publications
0
2
0
Order By: Relevance
“…2). Decades after its accidental introduction in Italy (Colazza et al 1996), T. pennipes not only established itself in the European continent, reaching as far north as the Netherlands (Zeegers 2010), it also managed to invade Asia, where it was recorded for the first time in Israel (Freidberg et al 2011), and afterwards Africa, where it was recorded in Egypt (El-Hawagry et al 2020). Bystrowski (2012) proposed two possible hypotheses concerning the presence of the species in Israel; the first being the expansion of T. pennipes from Italy through the coastal areas of Greece and Turkey, while the alternative hypothesis refers to an independent introduction event.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…2). Decades after its accidental introduction in Italy (Colazza et al 1996), T. pennipes not only established itself in the European continent, reaching as far north as the Netherlands (Zeegers 2010), it also managed to invade Asia, where it was recorded for the first time in Israel (Freidberg et al 2011), and afterwards Africa, where it was recorded in Egypt (El-Hawagry et al 2020). Bystrowski (2012) proposed two possible hypotheses concerning the presence of the species in Israel; the first being the expansion of T. pennipes from Italy through the coastal areas of Greece and Turkey, while the alternative hypothesis refers to an independent introduction event.…”
Section: Discussionmentioning
confidence: 99%
“…Skuhravá et al (2010) reported the fly's presence in Albania, yet no data were provided to support this claim. In addition, T. pennipes has been found in Africa (Egypt;El-Hawagry et al 2020) and Asia (Israel; Freidberg et al 2011), but it remains unknown whether it arrived there through direct spreading from Italy or by a separate introduction event (Bystrowski 2012).…”
Section: Introductionmentioning
confidence: 99%